Method of estimation of technical preparedness level of baseballs aged 12-14 years - Agapov, D. V.; Krovyakov, V. F.; Boyko, U. G.; Hodorchenko, V. M. (Physical Education of Students, 2013)
The method of estimation of level of technical preparedness is developed for young baseballs. The scale of estimation of level of technical preparedness of sportsmen is formed on the method of sigmantion rejections. In an experiment took part 100 boys in age 12-14 years. The test of the program «Aquafina MLB Pitch was utillized, Hit & Run». The maximally attained indexes are certain on separate baseball skills. The level of development of technical preparedness is exposed after an experiment on the program: a test of «pitch» is 450 marks, a test of «hit» is 402 marks, a test of «run» is a 361 mark, indexes of general marks are 1043 marks. The comparative analysis of level of technical preparedness of baseballs of control and experimental groups is conducted. Authenticity of distinctions is proved between control and experimental groups on the followings criteria of technical preparedness: throw, blow at run.